10th Lorne Infection and Immunity Conference 2020. Issue 10 (22nd November 2020) - Smith, Rebecca E; Drummer, Heidi E; Hertzog, Paul J
Abstract : The December 2020 issue contains a Special Feature on Infection and Immunity, featuring selected presentations from the 10th Lorne Infection and Immunity Conference. The breadth and excellence of science presented at this meeting is encompassed by the articles in this issue by Lamiable et al ., Saunders et al . and Chua et al .